An Advanced Study to Validate Synthesized Speech Parameterized by Cepstral Coefficients and LSP - Carlos Angel, Franco-Galván (New Visions in Science and Technology Vol. 9, 2021)
This document presents the results obtained from different statistical norms to validate the quality of synthesized voices applied to an HTS-based spanish synthesizer. Two parameterizations were tried out: LSP and Cepstral Coefficients. Standard MOS tests were carried out. MUSHRA, ABX and CCR where also conducted to reinforce the MOS results. A SUS test was employed to verify intelligibility.